A Water‐Containing Organopotassium Compound Based on Bis(4, 6‐tBu‐benzoxazol‐2‐yl)methanide and Its Unexpected Stability to Hydrolysis. Issue 47 (23rd October 2017) - Koehne, Ingo; Bachmann, Sebastian; Herbst‐Irmer, Regine; Stalke, Dietmar
Abstract: The bulky bis(4, 6‐ t Bu‐benzoxazol‐2‐yl)methane ligand system enabled the synthesis of the water‐containing organometallic potassium complex [(18‐crown‐6)K{(4, 6‐ t Bu‐OCNC6 H2 )2 CH}⋅H2 O] (2 ), which is an unprecedented example of a water‐stable reactive organopotassium compound. Furthermore, 2 is a rare example of a bis(benzoxazol‐2‐yl)methanide ligand displaying solely O‐coordination to a metal ion. Compound2 was fully characterized through its solid‐state structure. Furthermore, its behavior in solution was investigated by NMR titration DOSY experiments. These revealed full protonation of the complex only after seven days and the addition of 114 equivalents of water. Abstract : Fire and water are unified in a solely O‐coordinated organopotassium complex based on the ambidentate bis(4, 6‐ t Bu‐benzoxazol‐2‐yl)methanide ligand. The complex is fully protonated only after seven days and the addition of 114 equivalents of water, and might turn out to be a sustainable synthetic synthon in deep eutectic solvents.